Unusual Photoactive Water Oxidation Activity of Pt/PtOx Cocatalyst Decorated Crystalline α‐Fe2O3 Nanostructures: Exposed Facets Dependent Reactivity. Issue 8 (10th March 2020) - Patra, Astam K.; Amoli, Vipin; Sinha, Anil K.; Kim, Dukjoon
Abstract: A key challenge remains the preparation of an active and robust water oxidation photocatalyst with abundant earth materials. As a useful to improve photocatalytic efficiency, the development of α‐Fe2 O3 nanocrystals with different exposed facets and interfaces has attracted enormous attention. But literature survey shows that α‐Fe2 O3 nanomaterials were mainly used in photoelectrochemical cell for water splitting as anode materials. In this work, highly efficient Pt/PtOx cocatalyst decorated α‐Fe2 O3 shaped‐photocatalysts were derived as photocatalyst for white light‐induced O2 generation from water without any electric potential. The maximum apparent quantum efficiency of photooxidation reaction was reached 55.33 % by Pt/PtOx decorated bitruncated‐dodecahedron shaped α‐Fe2 O3 and around 30.5, 2.3, 1.28 times better than the Pt/PtOx decorated nanocuboid, nanorod and bitruncated‐octahedron shape respectively. The Pt/PtOx decorated bitruncated‐dodecahedron shaped α‐Fe2 O3 display an unusual photooxidation activity with a high TOF (1.96×10 −2  s −1 ) due to presence of destabilized and unsaturated Fe centre containing high energy {104} and {100} facets. The present findings clearly demonstrate that the selective O2 evolution from water can possible without any sacrificial agent. Abstract : The selective oxidation of water : The unusual oxidation of water to oxygen is shown by Pt/PtOx cocatalyst decorated crystalline α‐Fe2 O3 nanostructures without any sacrificial agent. However, the mechanism of the stepwise conversion is not fully understood. These photocatalyst display an unusual photooxidation activity with a high TOF (1.96×10 −2  s −1 ) and the activity varies with exposed facets and morphology of the nanocatalyst.